FORTALECIMIENTO TURISTICO SOSTENIBLE DEL PLAN DE DESARROLLO Y ORDENAMIENTO TERRITORIAL PARA LA PARROQUIA QUILANGA, CANTÓN QUILANGA, PROVINCIA DE LOJA - Cabrera Ojeda, Oscar Efrén (2019)
The tourism sector in Ecuador is a very important component for the generation of income, employment and production; It has allowed the growth of sectors of food, lodging, transport, intermediation, among others. Reason why it is necessary to plan adequately its development and the conservation of the resources used in it, through the necessary adoption of a vision of the long-term activity. The general objective of this research work is: To strengthen the Territorial Development and Planning Plan of the Quilanga parish, Quilanga canton, Loja province, "and for its fulfillment there are three specific objectives, the first objective: to carry out the diagnosis of the component tour of the Quilanga parish, Quilanga canton, province of Loja; for the development of this objective, techniques such as direct observation, interview, tourist diagnosis matrix of Carla Ricaurte Quijano, inventory tabs of tourist attractions of the Ministry of Tourism 2017, GPS were used, which helped us to determine the geographical coordinates, also He held a participatory workshop with the community and finally the SWOT matrix was made, which was essential to determine the current situation of the Quilanga parish. The second objective: To elaborate a tourism development proposal for the Quilanga parish through the application of a participatory methodology; for the development of this objective, the matrix of strategies was taken into account, from which four strategic objectives were obtained: Designing a tourism product, managing tourism planning in the Gad, promotion and publicity, and training, a second participatory workshop was held with the community For the development of the third objective: Propose strategies for the application of the proposed proposal for the tourist development of the Quilanga parish; To carry out this objective, different tourism strategies were proposed. The results obtained from the research work are the following proposals; preparation of a tourist route; which aims to enhance the natural and cultural attractions of the parish, the implementation of a tourist information center I-TUR that seeks to support the management of tourism in the parish, the design of a tourist guide based on providing complete information of the different attractions and touristic infrastructure of the parish, carried out in two languages and holding participatory workshops with the community; In addition, these proposals will make it possible to make the Quilanga parish known to tourists, as well as to help people generate a greater awareness of tourism and know the intrinsic value that they possess.